Manajemen Pendidikan dalam Keluarga Upaya Mewujudkan Keluarga Sakinah - Syaiful Bahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of the research was to analyze the management of education in family as the way to create a tranquil family. The method used in this research was qualitative descriptive method. The finding was the religous education in family consist of (1) pre and post natal education, (2) breast-feeding and sensitive period education, (3) childhood education, (4) adolescence education, (5) mature education and family education. In conclusion, education was required to be a tranquil family, begun from pre-natal to mature education. Keywords: Management, Religious Education, Tranquil Family